MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING, NUMBERED HEAD TOGETHER DAN TEAMS GAMES TOURNAMENT DI SDN SUNGAI MIAI 4 BANJARMASIN - Alfina Rahmah; Asrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The low activity, critical thinking skills, and mathematics learning outcomes in grade IV students of SDN Sungai Miai 4 Banjarmasin are due to the still dominant learning using the one-way method so that students are less actively involved. This is the background for the implementation of classroom action research with the aim of improving teacher and student activities, as well as critical thinking skills and learning outcomes through the application of Problem Based Learning, Numbered Head Together, and Teams Games Tournament learning models. This research was conducted in 4 meetings with 19 grade IV students of SDN Sungai Miai 4 Banjarmasin. The data collection technique uses observation sheets of teacher activities, student activities, critical thinking skills, and learning outcomes obtained through tests and non-tests both in groups and individually. The results of this study showed that teachers' activities increased from a score of 25 to 32 with the criterion of "Very Good". Student activity increased from 53% to 95% with the criterion of "Almost All Students Are Very Active". Critical thinking skills increased from 68% to 95% with the criterion of "Almost All Students Are Highly Skilled". The improvement of several aspects has an impact on cognitive student learning outcomes which increased from 68% to 100%. Affective learning outcomes from 63% to 89%. Psychomotor learning outcomes from 68% to 95%. It was concluded that the use of the Problem Based Learning, Numbered Head Together and Teams Games Tournament models could be carried out well in accordance with the steps of the learning process so as to improve students' activities, critical thinking skills, and mathematics learning outcomes.